Dual Modulus RSA Based on Jordan-totient Function. (2016) - Swami, Balram; Singh, Ravindar; Choudhary, Sanjay
Abstract: A public key cryptosystem consists of a public key, which is used for encryption, and a private key, used for decryption. Therefore, anybody can encrypt plain-text since the encryption key is available to everyone, but only the holders of the private key corresponding to the public key used for encryption can decrypt the cipher -text. RSA is the most popular Asymmetric cryptosystem as it uses pair of keys, one of which is used to encrypt the data in such a way that it can only be decrypted with the other key. The keys are generated by a common process, but they cannot be feasibly generated from each other. The security of the RSA system is based on the assumption that factoring of large number is difficult. But if one could factor a large number into its prime factors then he could break the security. So a new algorithm is developed to increase the security of RSA called Dual Modulus RSA based on Jordan-Totient function (DMRJT). DMRJT algorithm is more secure as compared to RSA algorithm as it uses dual modulus based double encryption and decryption with the use of Jordan function. It is shown here that dual modules play an important role in increasing the complexity of decomposing them into its factors and Jordan function increase the size of the private key hence increases the security. DMRJT algorithm uses double encryption and decryption using double private and public keys to provide security against Brute-force attacks.